2023
DOI: 10.1088/1742-6596/2578/1/012015
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Influencing Factors of the Compressive Strength of Planting Concrete

Ying Liu,
Dehua Liu,
Lijie Ma

Abstract: It is a study on the influence of aggregate size, water-cement ratio, and target porosity on the compressive strength of planting porous concrete. Experiment results show that porous concrete’s compressive strength is negatively correlated with target porosity and aggregate size; no distinct linear relation with the water-cement ratio is indicated, and there is an optimal water-cement ratio in different mix proportions. Among the three factors influencing the compressive strength of porous concrete, target por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Liu Ying et al conducted a comparative study on W/B, target porosity, and aggregate size. It was found that the influence of aggregate size on mechanical properties was slightly lower than the target porosity, but higher than the W/B [16].…”
Section: Introductionmentioning
confidence: 89%
“…Liu Ying et al conducted a comparative study on W/B, target porosity, and aggregate size. It was found that the influence of aggregate size on mechanical properties was slightly lower than the target porosity, but higher than the W/B [16].…”
Section: Introductionmentioning
confidence: 89%